Normative Review of The Dissolution of Limited Companies Proposed by Shareholders - Dana Arta, Erlangga; Putri, Aju; Janti (Alauddin Law Development Journal (ALDEV), 2024)
This study explains the legal framework governing the dissolution of Limited Liability Companies in Indonesia based on the Limited Liability Company Law (UUPT), with an emphasis on proposals encouraged by the General Meeting of Shareholders (GMS). Acknowledging the multifaceted nature of dissolution, this research emphasizes its far-reaching impact on employees, creditors, and society at large. The normative juridical approach is a methodological framework based on primary legal sources, which includes a comprehensive review of theories, concepts, legal principles and statutory regulations related to the subject matter under study. The legal consequence for a Limited Liability Company (PT) that does not undergo a liquidation process is that the company's continued existence remains, so that it is subject to ongoing legal obligations and administrative requirements which can result in sanctions and fines, while the inability to terminate legal entity status can complicate taxation issues. , licensing, and corporate governance.